A Rare Case of Malignant Glomus Tumor of the Esophagus - Gurvinder Singh Bali; Douglas J. Hartman; Joel B. Haight; Michael K. Gibson (Case Reports in Oncological Medicine)
Glomus tumors are rare neoplasms that usually occur on the hands in a subungual location, or sometimes in palms, wrists or soles of the feet. They are described as purple/pink tiny painful lesions with a triad of pain, local point tenderness, and cold hypersensitivity. They are almost always benign, but rare malignant variants have been reported. They have also been reported to be present at unusual locations, like the lung, stomach, or liver. Gastrointestinal glomus tumors are extremely rare tumors and very few cases have been reported in the literature. Most that have been reported were usually benign in nature. A rare esophageal glomangioma, mimicking a papilloma, was reported in 2006. We report a case of glomangiosarcoma (malignant glomus tumor) in a 49-year-old female, who presented with symptoms of dysphagia including some spasm and hoarseness and subjective unintentional weight loss. On endoscopic exam, she was found to have a distal esophageal mass with malignant features. Radiologically, the mass had a size of about 8 cm on the CT scan without evidence of metastases. Pathology and immunostaining of the biopsy showed features resembling a malignant glomus tumor. She underwent an endoscopic and laparoscopic staging of the tumor along with ultrasound. Based on the laparoscopic findings, which were consistent with the preoperative diagnosis, she was scheduled for an esophagectomy. Histopathology and immunophenotypic features of the excised mass were consistent with a diagnosis of malignant glomus tumor.